1993
DOI: 10.1111/j.1476-5381.1993.tb13938.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor subtypes in human and guinea‐pig pulmonary tissues

Abstract: 1 In this study the endothelin (ET) receptor subtypes mediating contractions produced by ET-1 in human and guinea-pig pulmonary tissues were investigated. In addition the receptor responsible for ET-1-induced prostanoid release in human bronchus was determined.2 In human bronchus and human pulmonary artery ET-l (0.1 nM-0.3 JIM) was a potent and effective contractile agent (pD2 = 7.58 + 0.15, n = 6, and 8.48 + 0.11, n = 7, respectively). BQ-123 (1-10 JiM), a potent and selective ETA receptor antagonist, potentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
95
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 53 publications
(62 reference statements)
13
95
1
1
Order By: Relevance
“…For example, ET-1-induced contraction in guinea-pig bronchus was mediated predominantly via ETB receptors (Hay, 1992), although evidence for multiple receptor subtypes in this tissue has been reported (Tschirhart et al, 1991). Furthermore, ETB receptors were also primarily responsible for mediating ET-1-induced contraction in human bronchus (Hay et al, 1993). However, in rat trachea, both ETA and ET5 receptors coexisted in approximately equal proportions and mediated responses which made approximately equivalent contributions to ET-1-induced increases in airway smooth muscle tone (Henry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ET-1-induced contraction in guinea-pig bronchus was mediated predominantly via ETB receptors (Hay, 1992), although evidence for multiple receptor subtypes in this tissue has been reported (Tschirhart et al, 1991). Furthermore, ETB receptors were also primarily responsible for mediating ET-1-induced contraction in human bronchus (Hay et al, 1993). However, in rat trachea, both ETA and ET5 receptors coexisted in approximately equal proportions and mediated responses which made approximately equivalent contributions to ET-1-induced increases in airway smooth muscle tone (Henry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ET-1 may be involved in the regulation of vascular tone in the foetomaternal region during pregnancy since it has been found to increase to high levels in plasma during delivery (Nisell et al, 1990). Although the pharmacology of ETs has been extensively studied in blood vessels of various animal species (for a recent review see Rubanyi & Polokoff, 1994), few studies have been performed in vessels of human origin (Hemsen et al, 1991;Hay et al, 1993;Maguire & Davenport, 1995;Bacon & Davenport, 1996). The …”
Section: Introduction Methodsmentioning
confidence: 99%
“…However, the vast majority of the binding sites for ET-1 on bronchial smooth muscle cells consists of ET B receptors. Consequently, in humans and guinea pigs, the ET A receptor antagonist BQ-123 antagonized ET-1-induced contraction of the pulmonary artery, but had no effect on bronchoconstriction, which was, on the other hand, markedly enhanced by application of the ET B agonist sarafotoxin S6c (12). In line with these findings, there was no bronchodilating effect due to inhaled LU-135252 in our study; moreover, mean airway pressure of volume-controlled mechanical ventilation remained unchanged in both groups.…”
Section: Discussionmentioning
confidence: 99%